Disturbed progesterone signalling in an advanced preclinical model of endometriosis. Issue 1 (July 2021) - Esfandiari, Fereshteh; Heidari Khoei, Heidar; Saber, Maryam; Favaedi, Raha; Piryaei, Abbas; Moini, Ashraf; Shahhoseini, Maryam; Ramezanali, Fariba; Ghaffari, Firouzeh; Baharvand, Hossein
Highlights: Human endometriosis organoids represent attenuated response to progesterone. Eutopic endometriosis organoids represent hypermethylation for progesterone receptor. Ectopic endometriosis organoids don't show progesterone receptor hypermethylation. Abstract: Research question: Do human endometriosis organoids recapitulate aberrant progesterone signalling in the disease to serve as advanced experimental models for uncovering epigenetic mechanisms involved in attenuated progesterone response in endometriosis? Design: Initially, the organoids were established from acquired biopsies (women with and without endometriosis) and characterized by morphological, histological and immunostaining analyses. Results: A panel of endometriosis-related genes showed a pattern of expressions in cytochrome c oxidase subunit II ( COX2 ), matrix metalloproteinase 2 ( MMP2 ), MMP9, tissue inhibitor of metalloproteinase-3 ( TIMP3 ), transforming growth factor beta 1 ( TGF-β1 ), and zinc finger E-box binding homeobox 1 ( ZEB1 ), and a contradictory expression pattern for cadherin ( CDH1 ), POU class 5 homeobox 1 ( POU5F1 ; also known as OCT4 ), and Nanog homeobox ( NANOG ) in the endometriosis organoids that is concordant with published research. These endometriosis organoids failed to upregulate 17β-Hydroxysteroid dehydrogenase 2 ( 17HSDβ2 ), progestogen associated endometrial protein ( PAEP ), secreted phosphoprotein 1 ( SPP1 ), and leukaemia inhibitory factor ( LIF ) in response to progesterone at the level observed in control endometrium organoids. Progesterone receptor B (PRB) gene expression significantly decreased in both eutopic and ectopic organoids compared with control endometrium organoids. DNA hypermethylation, as an epigenetic mechanism for suppression of transcription, was detected at the PRB promoter in the eutopic, but not ectopic, organoids. Therefore, other epigenetic mechanisms, such as histone modifications and microRNAs, may be responsible for PRB downregulation in ectopic organoids. Conclusions: Endometriosis organoids are powerful preclinical models that can be used to investigate the molecular mechanisms involved in endometriosis-associated progesterone resistance.